Pemanfaatan Abu Limbah Bonggol Jagung Sebagai Filler Aspalt Concrete Wearing Cource ( AC-WC ): Use Of Corn Cob Waste Ash As A Filler In Asphalt Concrete Wearing Course (AC-WC) - Alzahri, Syahril; Firnando, Fery (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
This study aims to determine how the results of the effect of the addition of corncob waste additives with a percentage of 2%, 3%, 4%, 5% on asphalt mix Asphalt Concrete - Wearing Course AC-WC with Marshall Test testing. The problems in this study are 1). The potential of natural resources that are not utilised. 2). Lack of public knowledge about the use of corncob waste, so that this research can provide knowledge to the public that corncob waste can be used as an added material for asphalt mixtures. 3). Reduced agricultural land area due to the large accumulation of unmanaged corn stalk waste. The method in this research is the experimental method, which is a method carried out by conducting experimental activities to obtain data. In this study, testing was carried out in stages, consisting of testing aggregates (fine, coarse, and filler) and asphalt and testing the mixture (marshaall test). The results of this study provide the results of the effect of the addition of corncob ash waste with variations of 2% and 3% can be used as an added material for asphalt mixtures because it meets and complies with the 2018 rev 2 bina marga specifications, while the addition of corncob waste with variations of 4% and 5% cannot be used as an added material for asphalt mixtures because the resulting value is not in accordance with the 2018 rev 2 bina marga specifications because the value of VIM does not meet the specifications of the 2018 rev 2 bina marga.